Comparability of thyroid-stimulating hormone immunoassays using fresh frozen human sera and external quality assessment data. - Shunli Zhang (Public Library of Science (PLoS), 2021)
Background This study aimed to assess the comparability among assays using freshly frozen human sera and external quality assessment (EQA) data in China. Methods Twenty-nine serum samples and two commercial EQA materials, obtained from the National Center for Clinical Laboratories (NCCL), were analyzed in triplicate using eight routine TSH assays. The commutability of commercial EQA materials (NCCL materials) was evaluated in accordance with the CLSI EP30-A and IFCC bias analysis. Median values obtained for the NCCL EQA materials were used to determine the systematic and commutability-related biases among immunoassays through back-calculation. The comparability of TSH measurements from a panel of clinical samples and NCCL EQA data was determined on the basis of Passing-Bablok regression. Furthermore, human serum pools were used to perform commutable EQA. Results NCCL EQA materials displayed commutability among three or five of seven assay combinations according CLSI or IFCC approach, respectively. The mean of systematic bias ranged from -13.78% to 9.85% for the eight routine TSH assays. After correcting for systematic bias, averaged commutability-related biases ranged between -42.26% and 12.19%. After correction for systematic and commutability -related biases, the slopes indicating interassay relatedness ranged from 0.801 to 1.299 using individual human sera, from 0.735 to 1.254 using NCCL EQA data, and from 0.729 to 1.115 using pooled human serum EQA(the commutable EQA). Conclusions The harmonization of TSH measurement is challenging; hence, systematic and commutability-related biases should be determined and corrected for accurate comparisons among assays when using human individual serum and the commercial EQA materials.